2020
DOI: 10.1007/s00264-020-04544-7
|View full text |Cite
|
Sign up to set email alerts
|

The plate fixation strategy of complex proximal humeral fractures

Abstract: Purpose For complex proximal humeral fractures, severe displacement and comminuted fragments lead to poor clinical outcomes. Despite considerable management, the locking plate fixation is still a preference and the proper selection of its strategy for each individual seems to be essential. Method The available classification system of the fracture, determination of surgical intervention, the common complications and related causes, and the latest critical surgical strategies with locking plate fixation were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…The maximum equivalent stress distribution of the internal fixation is an important criterion to measure the quality of the internal fixation. The internal fixation should have a uniform stress distribution and a small maximum equivalent stress value [2]. Under the three working conditions, the maximum Von Mises stress on the internal fixation is mainly distributed near the broken end of the fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum equivalent stress distribution of the internal fixation is an important criterion to measure the quality of the internal fixation. The internal fixation should have a uniform stress distribution and a small maximum equivalent stress value [2]. Under the three working conditions, the maximum Von Mises stress on the internal fixation is mainly distributed near the broken end of the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Humeral fractures often occurs in ball games, such as throwing or arm-wrestling movement, can also be found in a car accident injury, machine and scratches. Currently, the clinical treatment of middle and proximal humeral fractures is conventionally performed by interlocking intramedullary nail or locking plate percutaneous internal fixation [2][3]. Although some scholars think that these fractures can be treated without surgery [4], a recent study, involving a randomized controlled trial, concluded that surgical plating has a statistically significant advantage with a greater function, more rapid bone union, and lower deformity rate [5].…”
Section: Introductionmentioning
confidence: 99%
“…We reanalyzed the included literature by excluding each piece one at a time, and after excluding Fraser's (21) literature, we discovered that the reoperation rate SUCRA values for LP were significantly higher than HA. This finding may be related to the fact that, despite being consistently categorized as locking plate internal fixation, the technique of the procedure and the plates have been evolving over time (32)(33)(34). This implies that the results of earlier human research need to be viewed with greater objectivity because improved surgical procedures and plates may have reduced the incidence of negative events like reoperation rates for LP-treated proximal humeral fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Most publications on locking plates insist on the difficulty of achieving stable fixation in the event of severe displacement and comminuted fragments [17]. Large, prospective, multicentre trials by Südkamp et al [18] and Brunner et al [19] showed that internal fixation with locking plate was associated with good functional outcome but with a high percentage of implant-related complications (particularly primary and secondary screw perforation).…”
Section: Discussionmentioning
confidence: 99%